Do the port health officers at Soekarno-Hatta International Airports and Zainuddin Abdul Madjid International Airports have sufficient knowledge, attitude, and practice regarding emergency landing? - Herqutanto Herqutanto; Albert Wijaya; Budi Sampurna; Manaor F.L. Napitupulu; Ferdi Afian (Health Science Journal of Indonesia, 2021)
Background: : Emergency landing as an airport emergency requires quick and precise action by Port Health Office (PHO) as the medical coordinator. Medical treatment in an emergency landing is critical for the safety of disaster victims, based on the knowledge, attitudes and behavior of airport PHO officers. This study aimed to determine knowledge, attitude and behavior of PHO officers at Soekarno-Hatta International Airport (SOETTA) and Zainuddin Abdul Majid International Airport (ZAM) regarding emergency landings. Methods: This is an observational applying cross sectional design. Ninety-eight PHO officers from SOETTA airport and ZAM airport have participated, and their data was collected through questionnaires, and then analyzed based on knowledge, attitude, and practice toward emergency landing. Results: The knowledge of SOETTA PHO officers was sufficient in 63.5% officers, while it was 79.2% in ZAM. SOETTA PHO officers’ attitude was positive in 67.6% while in ZAM it was 54.16%. The behavior of SOETTA PHO officers was good in 55.4% officers while in ZAM it was 75%. Conclusion: The level of knowledge of SOETTA and ZAM PHO officers regarding emergency landings was sufficient. The attitude of SOETTA and ZAM PHO officers regarding emergency landings was positive. The behavior of SOETTA and ZAM PHO officers was good for emergency landings. Keywords: emergency landing, port health officer, knowledge, attitudes and practice Abstrak Latar belakang: Emergency landing sebagai salah satu keadaan darurat bandara memerlukan tindakan yang cepat dan tepat oleh Kantor Kesehatan Pelabuhan (KKP) sebagai koordinator medis. Penanganan medis dalam emergency landing sangat menentukan keselamatan dan keamanan korban, yang berbasis pada pengetahuan, sikap dan perilaku petugas KKP bandara. Penelitian ini bertujuan untuk mengetahui tingkat pengetahuan, sikap dan perilaku petugas KKP Bandara Internasional Soekarno-Hatta (SOETTA) dan Bandara Internasional Zainuddin Abdul Majid (ZAM) terhadap emergency landing. Metode: Penelitian ini adalah sebuah studi obervasional dengan disain potong lintang. Sembilan puluh delapan petugas KKP dari 74 bandara SOETTA dan 24 bandara ZAM diambil datanya lewat kuesioner.dan selanjutnya dinilai pengetahuan, sikap dan perilaku terhadap emergency landing. Hasil: Sebanyak 63,5% petugas KKP SOETTA memiliki pengetahuan yang cukup sementara 79,2% petugas ZAM meiliki pengetahuan yang tergolong cukup. Untuk hasil sikap petugas KPP SOETTA yang tergolong positif 67,6% sementara di ZAM sikap petugas KPP yang tergolong positif 54,16%. Untuk hasil perilaku petugas KPP SOETTA yang tergolong baik 55,4% sementara di ZAM perilaku petugas KPP yang tergolong baik 75%. Kesimpulan: Tingkat pengetahuan petugas KKP SOETTA dan petugas KKP ZAM terhadap emergency landing tergolong cukup. Sikap petugas KKP SOETTA dan ZAM terhadap penanganan emergency landing positif. Perilaku petugas KKP SOETTA dan ZAM cukup baik terhadap emergency landing. Kata kunci: emergency landing; petugas KKP; pengetahuan, sikap dan perilaku